4y - 3(y + 8) = 12
4y -3y - 24 = 12
y -24 =12
y = 36
2007-01-04 12:15:42
·
answer #1
·
answered by Sofia 2
·
0⤊
0⤋
I do like the y = 36 answer however if your interested in a bit of lateral thinking:
4y -3(y + 8) = 12?
then
4y -3y -3x8 = 12?
so
y - 24 = 12?
hence
y = 12? + 24
There's your function where ? is a parameter or another function! As you can see no matter the size of the value of ?, y is relatively big, eg
if ? = 1, then y =36
Aint that noice!
2007-01-04 20:34:44
·
answer #2
·
answered by Eric G 2
·
0⤊
0⤋
First: use distribution to eliminate the parenthesis > multiply 3 by both terms in the parenthesis >
4y - 3(y) - 3(8) = 12
4y - 3y - 24 = 12
Sec: combine "like" terms > combine coefficients with the same variable >
y - 24 = 12
Third: solve for "y" and keep it on one side > add 24 to both sides (opposite side means opposite sign) >
y - 24 + 24 = 12 + 24
y = 36
2007-01-04 20:16:42
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
4y - 3(y + 8) = 12
4y - 3y - 24 = 12
y = 36
2007-01-04 20:12:53
·
answer #4
·
answered by JasonM 7
·
0⤊
0⤋
4y-3y-24=12
+24 +24
y=36
2007-01-04 20:15:34
·
answer #5
·
answered by dance_babe_xoxoxox 2
·
0⤊
0⤋
4y - 3(y + 8) = 12
4y-3y+24=12---you do 3 x the y and 3x 8
then add the y values together 1y+24= 12
then subtract 24 from the 12 1y+24=12
-24 -24
to then equal 1y=-12
then divide by one /1 /1
and your final answer is y=-12 because negative divided by posative is still negative
hope that helps
2007-01-04 20:23:05
·
answer #6
·
answered by Amers 3
·
0⤊
0⤋
4y-3y-3*8=12
y-24=12
y=12+24
y=36
2007-01-04 20:18:20
·
answer #7
·
answered by Anis Z 1
·
0⤊
0⤋
4y-3(y+8)=12
4y-3y-24=12
y-24=12
y=36
2007-01-04 20:16:00
·
answer #8
·
answered by Micky [momo]♥ 2
·
0⤊
0⤋
y=36
2007-01-04 20:20:39
·
answer #9
·
answered by dani 2
·
0⤊
0⤋
4y-3y-24=12
y-24=12
y=36
2007-01-04 20:18:03
·
answer #10
·
answered by Mike 3
·
0⤊
0⤋